Pengaruh Endorsement Influencer dan Online Customer Review terhadap Minat Beli serta Implikasinya Pada Keputusan Pembelian: (Studi pada Rumah Makan Mandarin 28 Tretes, Pasuruan) - Yustika Pramaisela Febrianti; Survival Survival; Choirul Anam (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to empirically examine and analyze the influence of influencer endorsement and online customer reviews on purchase intention and their implications for purchase decisions. The research adopts a quantitative approach with an explanatory design. The population consists of consumers of Rumah Makan Mandarin 28 Tretes, Pasuruan, who have been exposed to or interacted with influencer endorsements and/or related online customer reviews, as well as those who have prior experience or potential interest in purchasing at the restaurant. A total sample of 100 respondents was determined, considered adequate for Partial Least Squares–Structural Equation Modeling (PLS-SEM) analysis with a medium-complexity model, and consistent with Roscoe’s guidelines (30–500 respondents). The findings reveal that influencer endorsement has a positive and significant effect on purchase decisions. In contrast, online customer reviews show no significant effect on purchase decisions. Furthermore, influencer endorsement exerts a positive and significant effect on purchase intention. Purchase intention is found to partially mediate the effect of influencer endorsement on purchase decisions, but it does not mediate the relationship between online customer reviews and purchase decisions. These results emphasize the importance of influencer endorsement in shaping both consumer purchase intention and purchase decision-making, while online customer reviews do not play a substantial role in this context. The study contributes to the understanding of consumer behavior in the digital marketing era, particularly within the restaurant industry, and provides managerial implications for businesses in developing effective marketing communication strategies through influencer collaboration.